Jawabanmu

2014-02-17T17:45:47+07:00
 x^{2} -5x+6 = (x-3)(x-2)
x1 = 3,x2 = 2

x1-3 = 3-3 = 0
x2-3 = 2-3 = -1

[x-(x1-3)][x-(x2-3)] 
x(x+1) =  x^{2} +x

22 3 22
2014-02-17T17:50:58+07:00
X1 . x2 = c/a = 6
x1 + x2 = -b/a = 5
anggap y1 = x1 - 3 dan y2 = x2 - 3
y1 + y2 = (x1 - 3) + (x2 - 3)
            = x1 + x2 - 6
            = 5 - 6 = -1
y1 . y2 = (x1 - 3) (x2 - 3)
           = x1.x2 -3x1 -3x2 + 9
           = 6 -3(x1 + x2) + 9
           = 6 -3 . 5 + 9
           = 6. -15 + 9 = -80 + 9 = -71
jadi persamaan kuadrat baru
x² - (y1 + y2)x + (y1y2) = 0
x² - (-1)x + (-71) = 0
x² + x -71 = 0

12 3 12